Local Dielectric Breakdown Path along c‐Axis Planar Boundaries in Cr2O3 Thin Films. Issue 20 (10th August 2017) - Sun, Congli; Song, Zhewen; Rath, Ashutosh; Street, Michael; Echtenkamp, William; Feng, Jie; Binek, Christian; Morgan, Dane; Voyles, Paul
Abstract: The 3D atomic structure of an interface‐stabilized planar boundary in the magnetoelectric Cr2 O3 thin films is reported based on scanning transmission electron microscopy as a function of scattering angle. Local boundary electron energy loss spectroscopy shows a prepeak on the O–K edge arising from unoccupied O 2p states. Density functional theory calculations reproduce the images and spectra and show that the boundary has smaller bandgap than bulk Cr2 O3, but does not interrupt the (0001) surface spin polarization and boundary magnetization. The reduced bandgap at the boundaries means they provide potential breakdown paths in Cr2 O3 thin films. The same planar defect is predicted to occur in other epitaxial corundum film/substrate systems. Abstract : Electron microscopy and spectroscopy experiments combined with density functional theory calculations show that interface‐stabilized planar boundaries in magnetoelectric Cr2 O3 films cause a local reduction in the bandgap, providing a potential dielectric breakdown path. The surface spin polarization is continuous across the boundary. Planar boundaries with similar structure are energetically favorable in other epitaxial corundum film/substrate systems.